Hello Puppy! - Cowen-Fletcher, Jane (Somerville, Mass. : Candlewick Press, 2010)
A child spends time with her new puppy, learning what it means when puppy yawns, stretches, and sniffs.
002-005.
Keywords: Dogs -- Fiction; Animal babies -- Fiction